Correction to: Italian translation, cultural adaptation, and pilot testing of a questionnaire to assess family burden in inherited ichthyoses - May El Hachem; Damiano Abeni; Andrea Diociaiuti; Roberta Rotunno; Francesco Gesualdo; Giovanna Zambruno; Christine Bodemer (BMC, 2020)
The original article contains a misspelling of co-author, Christine Bodemer's name which is presented correctly in this Correction article.